Development of Novel Organometallic Sulfonamides with N-Ethyl or N-Methyl Benzenesulfonamide Units as Potential Human Carbonic Anhydrase I, Ii, Ix and Xii Isoforms Inhibitors: Synthesis, Biological Evaluation and Docking Studies - Mascayano-Collado, C; Muñoz-Osses, M; Muñoz-Osses, M (Elsevier Inc., 2024)
In the search of new cymantrenyl- and ferrocenyl-sulfonamides as potencial inhibitors of human carbonic anhydrases (hCAs), four compounds based on N-ethyl or N-methyl benzenesulfonamide units have been obtained. These cymantrenyl (1a-b) and ferrocenyl (2a-b) derivatives were prepared by the reaction between aminobenzene sulfonamides ([NH2-(CH2)n-(C6H4)-SO2-NH2)], where n = 1, 2) with cymantrenyl sulfonyl chloride (P1) or ferrocenyl sulfonyl chloride (P2), respectively. All compounds were characterized by conventional spectroscopic techniques and cyclic voltammetry. In the solid state, the molecular structures of compounds 1a, 1b, and 2b were determined by single-crystal X–ray diffraction. Biological evaluation as carbonic anhydrases inhibitors were carried out and showed derivatives 1b y 2b present a higher inhibition than the drug control for the Human Carbonic Anhydrase (hCA) II and IX isoforms (KI = 7.3 nM and 5.8 nM, respectively) and behave as selective inhibition for hCA II isoform. Finally, the docking studies confirmed they share the same binding site and interactions as the known inhibitors acetazolamide (AAZ) and agree with biological studies. © 2024